Epididymitis in infants with anorectal malformation - KIYAN, GÜRSU (My University, 2003)
OBJECTIVE: To document the characteristics of epididymitis in boys with anorectal malformations. METHODS: Sixty-six boys with anorectal malformation were treated between January 1990 and January 2000, in our center. Four of these boys experienced epididymitis attacks. The first three patients had rectourinary fistula and the fourth had a low type anorectal malforation without a rectourinary fistula. RESULTS: Patients were followed up for seven to nine years and epididymitis did not recur after the definitive operation in the first three patients. The fourth patient had four other episodes of epididymitis postoperatively and no reason for these episodes could be found during the further urological evaluation. Two patients had urinary tract infection and one patient had urinary tract contamination during their episodes of epididymitis. CONCLUSION: The cause of the epididymitis can be anorectal malformation with rectourethral fistula itself or another urogenital anomaly that is associated with anorectal malformation. There is a relationship between urinary tract infection and epididymitis in these patients.
Keywords: Humans; Infant; Male; Urinary Tract Infections; Diagnosis, Differential; Recurrence; Rectal Fistula; Epididymitis; Urinary Fistula